Students Perspectives toward the Use of Instagram in Writing Class - Candradewi Wahyu Anggraeni (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This study presents the students perspectives of using Instagram in doing their writing assignment. Qualitative research method in the form of case study is conducted to obtain the data. Sixty students of writing class are employed as participants in this study. The result reveals that the students perspectives cover two aspects that include benefits and barriers of using Instagram. One of the benefits shows that participants have positive perspectives of using Instagram in their writing assignment. Participants view that Instagram is a valuable social network platform that motivate them to write better. However, the participants face challenges in using Instagram for their writing assignment. The overall contribution of this article is to build on theoretical, practical, and pedagogical significances for students perspectives toward using Instagram in writing class.